NSSR1 promotes neuronal differentiation of mouse embryonic carcinoma P19 cells - Liu, Lei; Chen, Xian-hua; Huang, Jia; Lin, Jun-ji; Lin, Wan-min; Xu, Ping (Neuroreport, 2004)
We generated the small interference RNAs to specifically silence the expression of neural salient serine/arginine rich protein 1 (NSSR1) and showed that the inhibition of NSSR1 expression in mouse embryonic carcinoma cells (P19) reduces neuronal differentiation. By contrast, its over-expression promotes the differentiation. Neither inhibition nor over-expression shows distinct effect on cell proliferation. The over-expression increases the inclusion of NCAM L1 exon2 while the inhibition reduces the inclusion. The splicing of kinase insert free isoform of TrkC (TrkC-K1) is increased by the over-expression. The results demonstrate that NSSR1 promotes neuronal differentiation and the splicing of NCAML1 exon2 and TrkC-K1.